Role of deformation mechanisms and grain growth in microstructure evolution during recrystallization of Mg-Nd based alloys. (June 2019) - Zeng, Xun; Minárik, Peter; Dobroň, Patrik; Letzig, Dietmar; Kainer, Karl Ulrich; Yi, Sangbong
Abstract: The microstructure and texture evolution during static recrystallization of Mg-Nd alloys were investigated. Depending on the third alloying element added into Mg-Nd alloy, either Al or Zn, diverse textures are formed during recrystallization annealing. The rolled Mg-2Nd-1Zn sheet shows a high activity of prismatic slip and the formation of a weak texture with basal pole spread in the sheet transverse direction. In contrast, a strong texture with a basal pole spread in the rolling direction was formed in the Mg-2Nd-1Al sheet. An equivalent growth of the recrystallized grains at the early annealing stage retains their orientations during grain growth. Graphical abstract: Unlabelled Image